An optimisation model for manufacturing outsourcing with application to semiconductor assembly. - Hia, Swee Chay. (2009)
In this dissertation, we develop an optimisation model for manufacturing outsourcing with special application to semiconductor assembly. The model is formulated using Linear Programming with the objective of maximising the firm's profit. It captures the relationships of the various variables such as the firm's in-house manufacturing resources, the utilisation of these resources, and the manufacturing outsourcing pricing structures. The model computes the maximum profit based on the relationships of these various variables. The output of the model includes the computed profit, the apportion of the volume demand of the product between the in-house manufacturing and manufacturing outsourcing activities, the slack of the in-house manufacturing resources.